Knowledge about Folic Acid Supplementation for Prevention of Neural Tube Defects among Gynecologist and Paediatric Surgeon - Sharif, Muhammad; Aqsa; Sharif, Muhammad Soban; Arif, Hafiz Muhammad; Hassan, Ahmad; Javaria (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the knowledge of gynecologist & Paediatric Surgeon about the role of folic acid in prevention of neural tube defects. Study design: Cross Sectional Study Setting & duration of study: Department of Paediatirc Surgery, KEMU/Mayo Hospital Lahore from 1st November to 15 December. Methodology: After ethical approval data was collected on a questioner performa created on google doc regarding demographic variables, knowledge about neural tube defects, dose and timing of folic acid supplementation in prevention of neural tube birth defects. Results: 70% of the doctor who took part in this study work between 20-30 year of age. 50% were male & 50% were female. Majority of doctors (80%) have experience of 1-10 years after graduation. The participants doctors include postgraduate residents (68%) followed by consultant (11.1%), Medical Officer, Senior Registrar, Registrar & House Officer. 90.7% were government employee most of them have knowledge about meningomylocele but majority of them (57.4%) did not have proper knowledge about dose and timing of folic acid supplementation for prevention of neural tube defects. Conclusions: We conclude that most of gynecologist and paediatric surgeons don’t have sufficient knowledge about role of folic acid in prevention of neural tube defects, specially meningomyelocele in children. There is a need to launch awareness campaign among healthcare providers through social media, symposium, and newspaper about supplementation of folic acid before conception in women so that this important disability condition/disease incidence may be reduced